THE CONCEPT OF "RAISING LEGAL CULTURE IN SOCIETY" AS A SOCIO-POLITICAL BASIS FOR IMPROVING THE LEGAL COMPETENCE OF YOUNG PEOPLE - G’.N. Pirnazarov (Galaxy International Interdisciplinary Research Journal, 2023)
In the current period, raising the legal culture of young people is one of the important conditions for building a civil society. Therefore, the fact that the state undertakes the main expenses necessary for legal and educational promotion shows that attention is being paid to the improvement of legal culture in our country at the level of state policy. In particular, the issue of raising the legal culture of young people and encouraging them to improve in all aspects is one of the issues under the special attention of our government.